Sarcoidosis in bone. Issue 538 (August 1970) - Pygott, F.
Abstract : Radiologically demonstrable bone change is found in about one in every six patients with sarcoidosis. The hands and feet are affected and rarely the trunk, an unusual distribution for a disseminate disease. Osteoporosis, cortical thinning and mottled rarefaction are the earliest signs, followed by cystic changes due to the coalescence of adjacent lesions and perhaps pathological fractures. The nasal bones may be directly involved in patients with lupus pernio. Changes in the rest of the skull, in the spine and pelvis are rare and may be bizarre.